Hypothalamic dysfunction in overtrained athletes - Barron, J. L.; Noakes, T. D.; Levy, W.; Smith, C.; Millar, R. P. (The Journal of Clinical Endocrinology & Metabolism, 1985)
Some athletes who undertake strenuous training programs for a prolonged period of time develop the overtraining syndrome. The pathophysiology of the condition is unknown. Hypothalamic-pituitary function was studied by determining the hormonal responses to insulin-induced hypoglycemia in five asymptomatic male marathon runners during a 4- month period in which they ran 42-, 56-, and 92-km races and in four overtrained male athletes. The response of the asymptomatic runners was not different when tested 1 month before and within 48 h after the 42- and 92-km races. All four overtrained athletes presented with impaired training and racing times, apathy, and a heavy-legged feeling and were tested when overtrained and again after 4 weeks of rest. The plasma cortisol, ACTH, GH, and PRL responses to insulin-induced hypoglycemia in the four overtrained athletes were lower than their responses after the rest and lower than the responses of the asymptomatic runners. In both groups, the LH, TSH, and PRL responses to LHRH and TRH were normal. The impaired hormonal responses to insulin-induced hypoglycemia, with recovery after 4 weeks of rest, indicate hypothalamic dysfunction and may be a diagnostic marker of the overtraining syndrome.